Tradisi Tolak Bala Sebelum Tanam Padi pada Masyarakat Desa Simaroken Kabupaten Pasaman (Kajian Living Al-Qur’an) - Rahmat Imanda; Zulheldi Zulheldi; Widia Fithri; Edriagus Saputra (Hikmah, 2021)
The tradition of rejecting reinforcements carried out by the Simaroken Village community is a form of repellent to future disasters on the plants to be planted. Local people believe that by carrying out this tradition, they can avoid diseases to their plants. This study aims to describe the tradition of rejecting reinforcements before planting rice in the Simaroken village community, Pasaman Regency. This study uses a qualitative field research method (field research). To obtain the data of this study, the authors conducted observations, interviews and documentation with respondents such as the government, ulama, community leaders and the community in general. The findings of this study are that the Simaroken community believes that the tradition of rejecting reinforcements can keep them and their plants away from all harm. The traditional procession of rejecting reinforcements before planting rice is carried out by all local people by providing food, drinks that will be served at the event and the main menu, namely lamang sipuluik. Because the lamang made of sipuluik (sticky rice) is part of what is planted by the local community and as a symbol of the results of the plant. The tradition of rejecting reinforcements is led by a cleric with a procession starting with reading the letter Yasin, al-Ikhlas, al-falaq, al-naas and several other letters followed by the whole community and a prayer led by a cleric and ending with eating a meal together .